Mycobiota and Metarhizium isolated of borer worm larvae from the ruezno (Cydia caryana) - Rosales Macias, Diana; Samaniego- Gaxiola, José Alfredo; Márquez Guerrero, Selenne Yuridia; Gaytán Mascorro, Arturo; Chew Madinaveitia, Yasmín; Crispín del Rio, Zaida (Revista Mexicana de Ciencias Agrícolas, 2017)
The necessity of having native organisms with potential for the biological control of pests for walnut pecan, motivated the registration of the mycobiota and search for entomopathogens in larvae of the worm borer of the rinds (GBR) Cydia caryana. To do so, in the year 2013, in a walnut orchard in The Laguna Mexico, 5 000 rindss were collected and processed to extract GBR larvae, which were incubated in a humid chamber or soil. Of larvae obtained before September 12 and placed in soil recovered 9% of Fusarium spp. + Gliocladium spp., In contrast, both fungi appeared 40% in larvae obtained after that date. In larvae obtained in December and placed in a humid chamber, Fusarium + Gliocladium spp. appeared 80%. It was only evidently Metarhizium anisopliae as entomopathogens of 5% of GBR larvae placed in soil after September 12, this fungus was also entomopathogenic of the giant red mite Trombidium sp., Black aphid of the walnut Melanocallis caryaefoliae, Tick Rhipicephalus sanguineus, and ant red Solenopsis sp. The GBR larvae can be used as a trap to recover Metarhizium and probably other entomopathogenic fungi on the soil of pecan walnut orchards.